Cross-Gender Inovativeness of Using Code Switching in Indonesan TV Talk Show (e-Journal of Linguistics, 2020)
Speakers will usually choose the appropriate code (certainlanguages, dialects, or variations of the same language) whencommunicating. The use of code switching by inserting Englishwords, phrases, sentences, or clauses into Indonesian utterancesis the implication of a bilingual speaker. This paper aims atanalyzing the types and factors of using code switching by maleparticipants and female participants in Indonesian TV talk shows.Data in this study is taken from a corpus of transcribed spokentext (82.270 words in total) from total 17 episodes from two talkshows aired on two different television programs. The resultsshow that female and male participants in their roles as hosts,guests, and co-host switch codes in their speech. They can be saidto be creative and innovative speakers
Keywords: implication; speaker; television programs